Optimal commodity taxation when land and structures must be taxed at the same rate - Saku Aura; Thomas Davidoff (Center for Economic Studies and ifo Institute (CESifo), 2005)
We show that the optimal property tax rate rises with the ratio of land rents to structure and land development costs. California's high ratio of income to property tax revenue and the distribution of Federal housing subsidies thus appear geographically misplaced. Proportional taxation of non-housing commodities is not optimal, even when elasticities with respect to wages are identical. Absent externalities, the desirability of transportation taxes and ?antisprawl? growth controls hinge on the relative importance of time versus money in commuting costs.
Keywords: R1; H21; 330; Grundsteuer; Verbrauchsteuer; Optimale Besteuerung; Bodenpreis; Bodenpolitik; Theorie; USA